2016
DOI: 10.1089/neu.2015.4163
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation with Valproic Acid Alters Inflammatory Genes in a Porcine Model of Combined Traumatic Brain Injury and Hemorrhagic Shock

Abstract: Traumatic brain injury and hemorrhagic shock (TBI+HS) elicit a complex inflammatory response that contributes to secondary brain injury. There is currently no proven pharmacologic treatment for TBI+HS, but modulation of the epigenome has been shown to be a promising strategy. The aim of this study was to investigate whether valproic acid (VPA), a histone deacetylase inhibitor, modulates the expression of cerebral inflammatory gene profiles in a large animal model of TBI+HS. Ten Yorkshire swine were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
(62 reference statements)
1
24
0
Order By: Relevance
“…A growing body of literature suggests that valproic acid may alter gene expression and protein functions following TBI (Dekker, 2014b; Halaweish, 2015b; Bambakidis 2016). Valproic acid has been in clinical use as a mood stabilizing and anti-epileptic and drug since the 1970s.…”
Section: Novel Resuscitation Techniques – Epigenetic Modulation Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature suggests that valproic acid may alter gene expression and protein functions following TBI (Dekker, 2014b; Halaweish, 2015b; Bambakidis 2016). Valproic acid has been in clinical use as a mood stabilizing and anti-epileptic and drug since the 1970s.…”
Section: Novel Resuscitation Techniques – Epigenetic Modulation Usingmentioning
confidence: 99%
“…The anti-inflammatory properties of valproic acid treatment have been described previously in models of sepsis, hemorrhage, and TBI (Shang, 2010; Jin, 2012a; Liu, 2014). In addition, Bambakidis et al (2016) showed that valproic acid modulates genes related to inflammation, cell signaling, cell adhesion, and endothelial growth. Dash et al (2010) furthermore showed that valproic acid treatment significantly decreased Evans Blue dye extravasation in a TBI rat model, indicating that valproic acid might restore BBB function following trauma.…”
Section: Novel Resuscitation Techniques – Epigenetic Modulation Usingmentioning
confidence: 99%
“…VPA administration also significantly downregulates genetic pathways involved in inflammatory responses . Administration of a single dose of VPA inhibited the complement system and natural killer intercellular communication, dendritic cell maturation, T cell, and B cell signaling and pattern recognition receptors in recognition of bacteria and viruses.…”
Section: Vpa Decreases the Genomic And Transcriptomic Changes Followimentioning
confidence: 99%
“…VPA administration alters multiple genomic changes following TBI. Using microarray technique, we studied the effects of VPA on brain gene expression in swine subjected to TBI (controlled cortical impact) and hemorrhagic shock (HS) . VPA was found to affect the expression of 370 well‐known genes following TBI and HS.…”
Section: Vpa Decreases the Genomic And Transcriptomic Changes Followimentioning
confidence: 99%
“…Treatment with fresh frozen plasma (FFP) has also been shown to be very effective, both as a monotherapy [17] and in combination with VPA—resulting in a synergistic effect [18]. VPA treatment up-regulates expression of beneficial genes in the injured brain [19,20], modulates posttraumatic brain metabolism [21], and improves long-term neurological recovery and healing [22] in clinically relevant models of TBI combined with HS.…”
Section: Pharmacological Treatment To Create a Prosurvival Phenotypementioning
confidence: 99%